Hyposalivation and oral health status among the Georgian population - Sophio Kakriashvili; Ann Margvelashvili; Zurab Artmeladze; Alexandre Pateishvili; Maria Nikuradze; Manana Kalandadze (Elsevier, 2021)
Introduction: The normal stimulated salivary flow rate averages 1.5-2.0 mL/min while the unstimulated - is approximately 0.3-0.4 mL/min. Below this average, it is considered hyposalivation. Hyposalivation may be an accompanying symptom of multiple chronic illnesses. Aim or Purpose: Salivary flow rate within the Georgian population is unknown. This study investigates hyposalivation in the Georgian population and examines if and how social conditions, liquid intake, and diseases influence hyposalivation. Materials and Methods: We examined 135 individuals (61 men and 74 women) of different age groups. Questionnaires were created to assess the general oral health condition, accompanying chronic diseases, and the daily amount of liquids intake.Participants were seated bent forward; the mouth was open while letting the saliva drip into a pre-weighed disposable cup for 10 min. The measurements were taken twice: to control unstimulated and stimulated salivary flow. Results: Hyposalivation was found in 19 healthy individuals, 27 patients with accompanying diseases, and 3 post-COVID-19 individuals - a total of 36.3 % of the examined individuals. Thus, 70% of the chronically ill and 33% of healthy individuals suffered from hyposalivation. Patients with hyposalivation revealed to bear a higher prevalence of dental caries (p-value 0.0009), increased dental wear (p-value < 0.0001), pathological changes of the oral mucosa (p-value 0.0012), and increased accumulation of dental plaque (p-value 0.0001). Conclusion: The study showed that although hyposalivation might be an accompanying symptom of several chronic illnesses and correlated to oral diseases, it can be compensated by the increase of the daily water intake.